2017
DOI: 10.1515/aep-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Removal of 4-chlorophenol from aqueous solution by granular activated carbon/nanoscale zero valent iron based on Response Surface Modeling

Abstract: NomenclatureRSM Response surface methodology BBD Box-Behnken factorial design AC Activated carbon NZVI Nano zero-valent iron SEM scanning electron microscope EDS electron dispersion spectrometer XRD x-ray diffraction PEG polyethylene glycol q e the amount of 4-CP adsorbed (mg l Keywords: response surface methodology, 4-chlorophenol, NZVI/AC.- Abstract:The phenolic compounds are known as priority pollutants, even in low concentrations, as a result of their toxicity and non-biodegradability. For this reason, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…7 a, b), the amount of O(II) decreased from 72.71 to 40.16% while the amount of C increased from 27.29 to 52.77% in the multimetal-loaded sample. In line with our results, Majlesi and Hashempour ( 2017 ) reported that the appearance of a peak at the energy level of Kα = 0.5 keV, Lα = 0.93 keV, and Mα= 8.91 keV deduced the successfulness of metal ion adsorption onto the fungal surface. Furthermore, Hoque and Fritscher ( 2019 ) stated that SEM-EDX analysis revealed the binding and precipitation of metal ions as spherical nano-particles (~50–100 nm) at the outer electro-negative cell wall-surface of Mucor sp.…”
Section: Resultssupporting
confidence: 92%
“…7 a, b), the amount of O(II) decreased from 72.71 to 40.16% while the amount of C increased from 27.29 to 52.77% in the multimetal-loaded sample. In line with our results, Majlesi and Hashempour ( 2017 ) reported that the appearance of a peak at the energy level of Kα = 0.5 keV, Lα = 0.93 keV, and Mα= 8.91 keV deduced the successfulness of metal ion adsorption onto the fungal surface. Furthermore, Hoque and Fritscher ( 2019 ) stated that SEM-EDX analysis revealed the binding and precipitation of metal ions as spherical nano-particles (~50–100 nm) at the outer electro-negative cell wall-surface of Mucor sp.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, many adsorbents have limited ability to adsorb phenols Yu 2006, Yousef andEl-Eswed 2009). Among others, carbonaceus and polymeric adsorbents, zeolites, and clays are used to remove phenol and chlorophenols from water (Damjanović et al 2010, Chen et al2017, Huang et al 2012, Hu et al 2012, Madannejad et al 2018, Majlesi and Hashempour 2017, Qiu et al 2014, Sarkar et al 2010, Su et al 2011, Yu et al 2004, Xie et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous removal studies regarding contaminants, using various methods such as granular activated carbon/nanoscale zero valent iron (Majlesi and Hashempour 2017), electroless copper plating process (Thomas et al 2018a), sodium trithiocarbonate (Thomas et al 2018b), zeolite bearing tuff (Zendelska et al 2018), and UV-Fenton method (Thomas et al 2018c). Various contaminants such as textile dye (Deshmukh et al 2016), persistent organic pollutants (Chakraborty and Das 2016), metals (Sidhoum and Fortas 2019), nanoparticles (Fikirdeşici-Ergen and Üçüncü-Tunca 2018) and polycyclic aromatic hydrocarbons (Kuppusamy et al 2016) were tested by removal studies.…”
Section: Introductionmentioning
confidence: 99%